Spark plasma sintering of B4C and B4C-TiB2 composites: Deformation and failure mechanisms under quasistatic and dynamic loading. Issue 6 (June 2021) - Rubink, W.S.; Ageh, V.; Lide, H.; Ley, N.A.; Young, M.L.; Casem, D.T.; Faierson, E.J.; Scharf, T.W.
Abstract: Spark plasma sintering (SPS) was employed to consolidate powder specimens consisting of B4 C and various B4 C-TiB2 compositions. SPS allowed for consolidation of pure B4 C, B4 C-13 vol.%TiB2, and B4 C-23 vol.%TiB2 composites achieving ≥99 % theoretical density without sintering additives, residual phases (e.g., graphite), and excessive grain growth due to long sintering times. Electron and x-ray microscopies determined homogeneous microstructures along with excellent distribution of TiB2 phase in both small and larger-scaled composites. An optimized B4 C-23 vol.%TiB2 composite with a targeted low density of ∼3.0 g/cm 3 exhibited 30–35 % increased hardness, fracture toughness, and flexural bend strength compared to several commercial armor-grade ceramics, with the flexural strength being strain rate insensitive under quasistatic and dynamic loading. Mechanistic studies determined that the improvements are a result of a) no residual graphitic carbon in the composites, b) interfacial microcrack toughening due to thermal expansion coefficient differences placing the B4 C matrix in compression and TiB2 phase in tension, and c) TiB2 phase aids in crack deflection thereby increasing the amount of intergranular fracture. Collectively, the addition of TiB2 serves as a toughening and strengthening phase, and scaling of SPS samples show promise for the manufacture of ceramic composites for body armor.